Virtual Reality Effect on Student Learning Outcomes in Nuclear Physics and Radioactivity Topics - Indira Gustaviana Nugroho; Rizqi Fajar Shidiq; Taufiq Al Farizi; Reza Ruhbani Amarulloh (Jurnal Penelitian Pembelajaran Fisika, 2025)
Learning Nuclear Physics and Radioactivity is often perceived as difficult by student because the concepts are abstract, thus requiring learning media that can visualize these concepts more concretely. This study aims to analyze the effect of using Virtual Reality media on student’s learning outcomes in the topic of Nuclear Physics and Radioactivity. The research employed a Quasi Experimental method with a Nonequivalent Control Group Design. The subject were 33 12th grade students of Al Adzkar High School, divided into two groups: an experimental group and a control group. The research instrument consisted of 20 multiple-choice questions mesuaring cognitive abilities from levels C2 to C6. The result indicated a significant difference between the control and experimental groups. The average post-test score of students in the experimental class (76.47) was higher than that of the control class (69.06). Improvement in learning outcomes was also reflected in the N-Gain score, which reached 0.57 (medium category) for the experimental class and 0.38 (medium category) for the control class. The analysis of cognitive indicators showed that improvement in the experimental class was more evenly distributed compared to the control class. Therefore, the use of Virtual Reality has been proven to enhance students learning outcomes by providing a more interactive and engaging learning experience, making it a potential alternative medium for classroom instruction.